ANALYSIS OF THE EFFECTIVENESS OF HSE PLAN ON WORK ACCIDENT CONTROL IN STRUCTURAL WORK AT BSI BANDA ACEH LANDMARK BUILDING CONSTRUCTION PROJECT - Rusda, Ikhsan; Abbas, Ibnu; Bulba, Alfa Taras (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2024)
Statistically, work accidents show a significant increase. The Social Security Organizing Agency (BPJS) Employment noted that the number of work accidents continues to increase by 5.65% every year. The purpose of this study is, and find out how the relationship between the effectiveness of HSE plan and risk control on the rate of work accidents. This study used a hypothesis test method, data collection was carried out using questionnaires to respondents of related parties. The closeness of the relationship between the two is included in the very strong (perfect) category, with a Pearson correlation value of 0.884. And it has a positive relationship which means that the higher the level of effectiveness of the HSE plan, the higher the level of work accident control. While the results of the coefficient of determination were obtained that the effectiveness of the HSE Plan affected the control of work accidents by 77.5%, while 22.5% of other things, the results of the hypothesis test simultaneously calculated table with a sig value of 0.05 and tcalculate ttable with a sig value of 0.05. This states that H0 is accepted and Ha is rejected, which means that there is an effect of the effectiveness of the HSE plan on simultaneous and partial control of work accidents. It can be concluded that the effectiveness of HSE Plan has a relationship and influence on work accident control. And it is expected that the next researcher will vary additional variables to be able to get an influence result of more than 80%.